2009
DOI: 10.1002/jbt.20304
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene expression profiles in K6/ODC mouse skin and papillomas following a chronic exposure to monomethylarsonous acid

Abstract: We have previously observed that a chronic drinking water exposure to monomethylarsonous acid [MMA(III)], a cellular metabolite of inorganic arsenic, increases tumor frequency in the skin of keratin VI/ornithine decarboxylase (K6/ODC) transgenic mice. To characterize gene expression profiles predictive of MMA(III) exposure and mode of action of carcinogenesis, skin and papilloma RNA was isolated from K6/ODC mice administered 0, 10, 50, and 100 ppm MMA(III) in their drinking water for 26 weeks. Following RNA pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…They showed that the effects of methylated metabolites on F344 female rats resulted in pathological changes of the bladder which were attributed to MMA(III) following DMA(V) treatments in the diet. Other studies have also provided some evidence of the carcinogenicity of MMA(III) in rodent models (Delker et al, 2009; Krishnamohan et al, 2006). In an attempt to elicit some type of toxicological response, researchers had employed very high concentrations of MMA(III) in these studies, far beyond the relevant levels of exposures in human populations.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the effects of methylated metabolites on F344 female rats resulted in pathological changes of the bladder which were attributed to MMA(III) following DMA(V) treatments in the diet. Other studies have also provided some evidence of the carcinogenicity of MMA(III) in rodent models (Delker et al, 2009; Krishnamohan et al, 2006). In an attempt to elicit some type of toxicological response, researchers had employed very high concentrations of MMA(III) in these studies, far beyond the relevant levels of exposures in human populations.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 101 genes that were differentially expressed between genotypes basally (Figure 1A). Web-based DAVID gene function organizing tool (22) allowed grouping of most of these 101 genes into 45 overlapping biological process categories. Five categories from this list include response to hypoxia, cell proliferation, transcription, apoptosis and metabolism that account for two thirds of the identified genes (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of MMA (III) in triggering malignant urothelial transformation during bladder cancer has been well studied (Medeiros et al, 2012;Wang et al, 2007;Wnek et al, 2010). There is limited data showing how MMA (III) potentiates skin cancer (Chen et al, 2008;Delker et al, 2009), or the role of MMA (III) in other arsenic induced diseases. One report on nanomolar levels of MMA (III) impairing vascular smooth muscle contractility in mice suggests that MMA (III) contributes to arsenicassociated cardiovascular diseases more potently than arsenite FIG.…”
Section: Discussionmentioning
confidence: 99%